ANALISIS DERAJAT DESENTRALISASI FISKAL DAN KEMANDIRIAN DAERAH KABUPATEN TULANG BAWANG BARAT DAN KABUPATEN PESISIR BARAT TAHUN ANGGARAN 2018-2020 - Rifky Febrihanuddin (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
Based on Law Number 23 of 2014 concerning Regional Government and Law Number 33 of 2004 concerning Financial Balance between Central and Regional Government. This regulation provides an opportunity for regions to explore potential financial performance in the context of realizing regional independence based on regional autonomy. This study aims to determine the level of independence in Tulang Bawang Barat and Pesisir Barat which is measured based on the degree of fiscal decentralization and regional independence as well as factors related to fiscal independence. The data used in this research is secondary data in the form of APBD for the 2018-2020 Fiscal Year. The data is Total Regional Revenue, Original Regional Revenue and Balancing Fund. This study uses a descriptive method with a quantitative approach. The results showed that the level of fiscal independence in Tulang Bawang Barat and Pesisir Barat showed an instructive or very low pattern of relationship, but the average ratio of the level of fiscal independence in Tulang Bawang Barat was higher than that of the West Coast, the contribution of local revenue to regional revenues was higher. in Tulang Bawang Barat rather than Pesisir Barat, the level of dependence on Central Government assistance in West Tulang Bawang Regency was also higher than that of Pesisir Barat Regency. Based on the analysis of factors related to fiscal independence in Tulang Bawang Barat and Pesisir Barat, including community participation, area size, and growth of gross regional domestic product.